STUDENTS ABILITY IN COMPREHENDING ENGLISH TEXTS - Sudiran, Sudiran (Jurnal Bestari, 1993)
Students will succeed in finishing their and to understand English texts. On the other hand, Students who cannot comprehend printed English books will have a number of problems because they are shortage of knowledge. As a result, it is very important for students to learn how to understand English texts.